2018
DOI: 10.1088/2399-6528/aac2a4
|View full text |Cite
|
Sign up to set email alerts
|

Effect of layered water structures on the anomalous transport through nanoscale graphene channels

Abstract: We analyse the enhanced flow rate of water through nano-fabricated graphene channels that has been recently observed experimentally. Using molecular dynamics simulations in channels of similar lateral dimensions as the experimental ones, our results reveal for the first time a relationship between water structure and the variation of flux in the rectangular graphene channels. The substantial enhancement in the flow rate compared to Poieseuille flow is due to the formation of layered 2D structures in the confin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 55 publications
2
16
0
Order By: Relevance
“…There have been several studies on the ordering of water inside a hydrophobic nanocapillary [29][30][31]33,34 . Particularly monolayer/bilayer ice confined within a hydrophobic nanochannel has been studied using MD simulations 30,31,33,35,36 and using density functional theory calculations 37 . Such an ordering of water molecules can change significantly the density 8,38,39 and its viscosity 31 inside the channel.…”
mentioning
confidence: 99%
“…There have been several studies on the ordering of water inside a hydrophobic nanocapillary [29][30][31]33,34 . Particularly monolayer/bilayer ice confined within a hydrophobic nanochannel has been studied using MD simulations 30,31,33,35,36 and using density functional theory calculations 37 . Such an ordering of water molecules can change significantly the density 8,38,39 and its viscosity 31 inside the channel.…”
mentioning
confidence: 99%
“…Further work is needed to unravel the features of water under ultra-confinement, where water could undergo structural and/or dynamical transitions. [102][103][104][105] In order to quantify the amount of hydrophobicity, we compute the contact angle of a liquid droplet located on a planar surface. As in an experimental drop-shape analysis [106], we prepare a liquid droplet containing 200 water molecules and locate it on top of a rigid and flat carbon surface.…”
Section: Discussionmentioning
confidence: 99%
“…Further work is needed to unravel the features of water under ultra-confinement, where water could undergo structural and/or dynamical transitions. [102][103][104][105] friction on the two walls. When the distance to the walls is large as compared to the particle radius, one can write [85,[87][88][89]:…”
Section: Discussionmentioning
confidence: 99%
“…20 A recent study also showed that water flux enhancement can be driven by pressure difference. 25 The two-dimensional graphene channels substantially differ from the one-dimensional CNTs 15,16 because of the fact that they accommodate two-dimensional water structures and offer precise control of channel sizes down to the atomic scale.…”
Section: ■ Introductionmentioning
confidence: 99%